How Perceived Managerial Behaviors Influence Employees’ Perception of Gender Equality: The Case of a French Organization - Coron, Clotilde (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
Few studies have examined the influence of perceived managerial behaviors on perceived workplace gender equality. This paper seeks to fill this gap by mobilizing the theoretical framework of organizational justice to study the case of a French company. 52 interviews were conducted to formulate the hypotheses and a survey was constructed to test them. The results indicate that perceived managerial behaviors have an influence on perceived gender equality. Female employees consider managerial compliance with policy and efforts to prevent female self-censorship important, whereas male employees consider managerial efforts to ensure gender diversity in recruiting and promoting important.